FORMATION OF WINTER WHEAT YIELD DEPENDING ON THE VARIETY AND METHOD OF TREATMENT WITH BIOLOGICAL PREPARATIONS IN THE WESTERN FOREST-STEPPE OF UKRAINE - Шейко, Денис (SWorldJournal, 2023)
Purpose. The aim of our research was to determine the dependence of biometric parameters and yield of winter wheat varieties depending on the methods of application of biologically active preparations in the Western Forest-Steppe of Ukraine. The research